SUSTAINABLE MODEL OF FUNCTIONING LOGISTICS FOR PERISHABLE GOODS SUPPLY THROUGH UKRAINIAN – POLAND ROUTES - Pavlenko О.; Muzylyov, D. (Municipal economy of cities. Series: «Economy science», 2023)
The paper highlights the current state and prospects for logistics development of perishable goods supply in international traffic, which made it possible to justify the study aim in this research. The chosen topic is quite relevant because developing supplies to European countries have a real perspective according to last tendencies in the international perishable goods market. This fact is additionally justified by increasing delivery volumes of milk and meat products, and animal fats every year. One of the directions for supply logistics cost reduction is an efficient use of transport resources (vehicles, warehouses). The scientific projects and their results have shown that a well-developed market for transport services with appropriate operators and infrastructure allows effective logistics implementation for perishable goods delivery in international traffic to costs reducing for all supply chain participants. A structural model has been designed for the sequential interaction of logistics participants during perishable goods supply on routes from Ukraine to Poland, which is formed from certain participants implementing relevant operations. The sequence is designed based on order analysis of transport enterprises by cargo order volumes, transportation distances, operations cost, operations time, as well as statistical data of corresponding parameters. Three alternative options for the logistics of perishable goods delivery were formed, using road transport with various load capacities and warehouses. The designed schemes consider opportunities for using a consolidation warehouse in Ukrainian territory for a possible combination of products and involving a perishable cargo distribution warehouse in Poland territory. The operation costs of relevant supply logistics variants are selected as a criterion for evaluating proposed solutions. These costs are affected by: operations cost; the volume of perishable goods batch; transportation distances; shippers (consignees) quantity; operation time parameters. The mathematical models’ components for logistics of perishable goods supply have been designed according to alternative three options, considering performing operations specifics at each stage, as well as the peculiarities of cost and time determining for each operation performing in the supply chain.